If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -2c = -9 + 7c Solving 9 + -2c = -9 + 7c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7c' to each side of the equation. 9 + -2c + -7c = -9 + 7c + -7c Combine like terms: -2c + -7c = -9c 9 + -9c = -9 + 7c + -7c Combine like terms: 7c + -7c = 0 9 + -9c = -9 + 0 9 + -9c = -9 Add '-9' to each side of the equation. 9 + -9 + -9c = -9 + -9 Combine like terms: 9 + -9 = 0 0 + -9c = -9 + -9 -9c = -9 + -9 Combine like terms: -9 + -9 = -18 -9c = -18 Divide each side by '-9'. c = 2 Simplifying c = 2
| 12-7x=6-x | | 4(w+5)-7w=38 | | 3.6=-2.9+5.8 | | 1/4-9=12 | | 3.6=-29+5.8 | | -3-j=-9-2j | | 9.10=k+7.10 | | (3x-4)-(6x+3)+(9x-4)= | | 2/x=18/27 | | 9h-3=10h | | 12+3q= | | (4x+1)+(x-1)+(x+1)=180 | | T-3=9 | | t^2+3r-2=0 | | -10-6w=-8w | | 2X+2-(4X-1-9X)=6X-1 | | 19-m=23 | | -7y+5y=-10+6 | | -2n+7=-n | | 3*(-1/2)(4^2)-(-3^3)/-1/2 | | 11x-4=55 | | 4x^2+9x-4=x^2-2x | | Y-5=4(y-5)-9 | | 61-11x=17-8x | | 4r=7+5r | | 16x*9y=214 | | 5(2-0.375)-9(0.125)=4(3-0.25) | | 7/9=1/3t | | (y-5)=4y-9 | | Y-7/8=-15/17 | | log(50x+250)-log=2 | | 4x-14=8x-47-(3x-14) |